Rural good oxygen pool system of sewage of solar energy based on thing networking - HE FEI; ZHANG DEJIN; XIE YUFENG; LI WEIXIN; LI ZHILIN (2018)
The utility model discloses a rural good oxygen pool system of sewage of solar energy based on thing networking, including solar electric system, the good oxygen pool system of rural sewage and main control unit, solar electric system includes solar cell panel, charge controller, battery and dc -to -ac converter, the rural good oxygen pool system of sewage includes support group spare, the good oxygen pool, flow velocity monitoring ware, the COD detector of intaking, goes out water COD detector, surface of water wind speed detector and dissolved oxygen detector, and surface of water wind speeddetector has been located the surface of water top on the oxygen pool, and flow velocity monitoring ware and dissolved oxygen detector all have been located the surface of water on the oxygen pool, main control unit is connected with flow velocity monitoring ware, the COD detector of intaking, play water COD detector, surface of water wind speed detector and dissolved oxygen detector respectively, the utility model discl